1991
DOI: 10.1126/science.1825142
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the c- mos Product to Associate with and Phosphorylate Tubulin

Abstract: The mos proto-oncogene product, pp39mos, is a protein kinase and has been equated with cytostatic factor (CSF), an activity in unfertilized eggs that is thought to be responsible for the arrest of meiosis at metaphase II. The biochemical properties and potential substrates of pp39mos were examined in unfertilized eggs and in transformed cells in order to study how the protein functions both as CSF and in transformation. The pp39mos protein associated with polymers under conditions that favor tubulin oligomeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…56,57 Microtubules are associated with serine/threonine kinases and phosphatases. [58][59][60][61] As the plasma membrane is an important source of signals during interphase, microtubules may be a principal location of signaling following mitotic arrest. Since mitochondria, an organelle where many members of the Bcl-2 family reside, 62 has proximity to microtubules, this may direct microtubule disruption to the apoptotic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Microtubules are associated with serine/threonine kinases and phosphatases. [58][59][60][61] As the plasma membrane is an important source of signals during interphase, microtubules may be a principal location of signaling following mitotic arrest. Since mitochondria, an organelle where many members of the Bcl-2 family reside, 62 has proximity to microtubules, this may direct microtubule disruption to the apoptotic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Mos binds to tubulin and has a role in the bipolar meiotic spindle formation (Zhou et al, 1991;Yew et al, 1993;Verlhac et al, 1996). At early meiosis I, Mos induces nucleation of multiple centrosomes in the vicinity of condensing bivalents.…”
Section: Roles Of Mos In Meiosismentioning
confidence: 99%
“…In this study, we further demonstrate from the GST pull-down assay that CagSpin directly or indirectly associates with h-tubulin, and therefore provide the first biochemical evidence for the specific interaction of Spindlin protein and h-tubulin, the microtubule component. Interestingly, some important proteins that play crucial functions during oocyte maturation and egg fertilization, such as p39 mos (Zhou et al, 1992;Haccard et al, 1993;Verlhac et al, 1996), p34 cdc2 of metaphase promoting factor (MPF) (Langan et al, 1989;Peter et al, 1990;Verde et al, 1990;Zhou et al, 1991Zhou et al, , 1992, cyclin B, the regulatory component of MPF (Pines and Hunter, 1991;Ookata et al, 1993), MAP kinase (Verlhac et al, 1993) and PKC (Page Baluch et al, 2004), have been also confirmed to associate with microtubules. Interestingly, three putative PKC phosphorylation sites have been revealed in the CagSpin sequence (Fig.…”
Section: Biochemical Evidence Of Association Between B-tubulin and Camentioning
confidence: 99%